EXPERIMENTAL METHODS TO ELUCIDATE LUNG EXTRACELLULAR MATRIX EFFECTS ON FIBROBLAST/MYOFIBROBLAST PHENOTYPE - Wheildon, Nolan (My University, 2015)
Introduction Idiopathic pulmonary fibrosis (IPF) is a debilitating restrictive lung disease with no curative treatments. Accumulation of lung extracellular matrix (ECM) and myofibroblasts are two hallmarks of this disease. Previous studies have demonstrated that an increase in lung ECM in the formation of scar tissue promotes further myofibroblast accumulation exacerbating IPF disease progression. Lung ECM influence on myofibroblast phenotype is not fully understood. Methods to elucidate lung ECM effects on myofibroblast phenotype were developed in this thesis. Aim This study sought to determine whether lung ECM could modulate fibroblast/myofibroblast phenotype. Methods Histological and western blot analyses were used to evaluate lung ECM isolation through manual decellularization of whole rat lungs with sodium deoxycholate (SDC). To evaluate the effects decellularization has on lung ECM, histological analyses were conducted to compare sodium dodecyl sulfate (SDS) and SDC ability to retain collagen and elastic fibers following decellularization. Histological examination of drop-wise and whole lung reseeding techniques of decellularized lung ECM were assessed. To further mimic in vivo conditions, a novel lung bioreactor incorporating physiological lung respiration and vascular perfusion was developed. The effects of stiff cell culture plastic on alpha smooth muscle actin (α-SMA) phenotype of control and IPF-derived myofibroblasts were evaluated. Western blot, immunohistochemisty, immunocytochemistry, and immunofluorescent analyses were used to evaluate whether normal lung ECM could reverse the α-SMA positive phenotype of lung myofibroblasts. Results Manual decellularization with SDC was effective at decellularizing whole rat lung. Histological examination showed that SDC was more effective at retaining collagen and elastic fibers than SDS following decellularization. Whole lung reseeding technique was far superior compared to the drop-wise technique at consistently reseeding lung ECM. Lung bioreactor maintained A549 cells within decellularized whole lung for 3 days. Furthermore, normal lung ECM was capable of reversing α-SMA positive phenotype of both control and IPF-derived myofibroblasts. Conclusions Methods developed in this thesis advances the understanding of decellularization and reseeding techniques required to study lung ECM on cell phenotype. Interestingly, and contrary to previous work, it appears that α-SMA phenotype of myofibroblasts was reversible when cultured on normal lung ECM.